Phonon-drag Contribution to Seebeck Coefficient of Ge-on-insulator Substrate Fabricated by Wafer Bonding Process - Manimuthu, Veerappan; Yoshida, Shoma; Suzuki, Yuhei; Salleh, Faiz; Arivanandhan, Mukannan; Kamakura, Yoshinari; Hayakawa, Yasuhiro; Ikeda, Hiroya (Makara Journal of Technology, 2015)
In order to build high-sensitivity infrared photodetectors using SiGe nanowires, we investigate the thermoelectric characteristics of Ge-on-insulator (GOI) layers as a reference for SiGe. We fabricate p-type GOI substrates with an impurity concentration of 1016-1018cm-3 by a wafer-bonding process using Ge and oxidized Si wafers. Annealing treatment is performed in order to further increase the bonding strength of Ge/SiO2 interface. We measure the Seebeck coefficient in the temperature range of 290-350 K. The Seebeck coefficient of the GOI layers is very close to the theoretical value for Ge, calculated on the basis of carrier transport. Hence, there is a small phonon-drag effect in GOI. On the other hand, the effect of phonon drag on the Seebeck coefficient of Si is usually significant. These results likely stem from the differences between phonon velocity, phonon mean-free-path, and hole mobility between Ge and Si.